2019
DOI: 10.2106/jbjs.18.01373
|View full text |Cite
|
Sign up to set email alerts
|

At a 10-Year Follow-up, Tendon Repair Is Superior to Physiotherapy in the Treatment of Small and Medium-Sized Rotator Cuff Tears

Abstract: Background: Tendon repair and physiotherapy are frequently used treatment methods for small and medium-sized rotator cuff tears. In 2 previous publications of the 1 and 5-year results of this study, we reported significant but small between-group differences in favor of tendon repair. Long-term results are needed to assess whether the results in both groups remain stable over time. Methods: In this study, 103 patients with a rotator cuff tear not exceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 39 publications
2
74
0
1
Order By: Relevance
“…It may also be speculated that the delay in orthopaedic surgical procedures may even lead to poorer postoperative outcomes. With this in view, Mossmayer et al prospectively followed 103 patients with rotator cuff tears over ten years and found that those with delayed repair had significantly poorer results than those who underwent early repair - an effect that worsened with every passing year [ 15 ]. The same was also studied in patients waiting for ACLR [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may also be speculated that the delay in orthopaedic surgical procedures may even lead to poorer postoperative outcomes. With this in view, Mossmayer et al prospectively followed 103 patients with rotator cuff tears over ten years and found that those with delayed repair had significantly poorer results than those who underwent early repair - an effect that worsened with every passing year [ 15 ]. The same was also studied in patients waiting for ACLR [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a well-performed prospective randomised study with long follow-up can overcome some of these difficulties. Ten year results with 88 % follow-up from such a study were recently published by Moosmayer et al 198 . The repair group had a better result for Constant score (by 9.6 points), as well as better scores for ASES, pain, pain-free abduction and pain-free flexion, with all differences being statistically significant.…”
Section: Acromioplasty Without Cuff Repairmentioning
confidence: 90%
“…Within that population patient outcomes following acute surgical intervention have been shown to be improved. Of note, recent data does suggest that even patients exhibiting small tears may have improved functional outcomes following surgical intervention [14].…”
Section: And 5 Respectively)mentioning
confidence: 99%